LcIMT1, a litchi inositol methyl transferase gene, is responsible for d-bornesitol biosynthesis and confers drought tolerance - Huang, Liang-Liang; Li, Xin-Ying; Liu, Fang-Fang; Huang, Xu-Ming; Zeng, Ren-Fang; Abbas, Farhat; Wang, Hui-Cong (Plant stress (Amsterdam), 2025)
•LcIMT1 generates d-bornesitol (1-O-methyl-myo-inositol), a precursor in the biosynthesis of quebrachitol, in litchi.•In drought stress, d-bornesitol and quebrachitol accumulation and LcIMT1 expression increased.•LcIMT overexpression in Arabidopsis, tomato, and tobacco led to increased production of d-bornesitol.•LcIMT-overexpressing tomato plants have higher photosynthetic and enzymatic activity. l-quebrachitol, also known as 2-O-methyl-l-chiro-inositol, is a common form of methylated cyclitol found in Litchi chinensis, accounting for more than half of the soluble sugars. Nonetheless, the biological function of l-quebrachitol is somewhat restricted. Herein, we target an inositol methyltransferase (LcIMT1) gene that generates d-bornesitol (1-O-methyl-myo-inositol), an intermediate of l-quebrachitol biosynthesis, in litchi. Litchi plants confronted with drought stress showed a substantial increase in methyl inositol (d-bornesitol and l-quebrachitol) levels and LcIMT1 expression in roots and leaves relative to control plants. Additionally, overexpressing LcIMT1 in arabidopsis, tomato, and tobacco resulted in an enormous increase in d-bornesitol production compared to the wild-type (WT). Furthermore, the transgenic tomato lines displayed higher drought resistance as reflected by less wilt, lower relative electrolyte leakage, enhanced Fv/Fm, and higher CO2 assimilation mainly due to higher stomatal conductance compared to the wild-type when underwent drought conditions. Better drought resistance in transgenic tomato lines might be associated with the accumulation of d-bornesitol which assists in maintaining cell turgor by reducing cell water potential and cellular homeostasis of reactive oxidant species (ROS). Reduced oxidative damage, as evidenced by diminished MDA levels and lower concentrations of superoxide and hydrogen peroxide, may stem from the heightened energy consumption by the photosynthetic apparatus for CO2 fixation and the reactive oxygen species scavenging capability of d-borneistol in the leaves of LcIMT1 overexpressed lines. The findings of this study indicate that LcIMT1 overexpression facilitates d-bornesitol biosynthesis, which functions as an osmotic regulator and free radical scavenger, thereby enhancing the drought resistance of tomatoes. Future research could investigate the exogenous application of myo-inositol methyl ether as a potential approach for mitigating dryness in plants. This research avenue possesses significant commercial prospects for agricultural applications, especially in water-scarce settings.